Mosquito Diversity in an Experimental Township in Tamil Nadu, India. Issue 5 (15th June 2022) - Visa Shalini, P; Shriram, A N; Elango, A; Natarajan, R; Vijayakumar, B; Raju, K H K; Dengel, Lucas; Gunasekaran, K; Kumar, Ashwani
Abstract: To glean more information on mosquito diversity and distribution in Auroville, a cross-sectional study was carried out by mapping the distribution of water bodies and habitats supporting immature stages on the one hand and the distribution of water bodies/habitats supporting mosquito immature stages on the other. A satellite image covering an area of 8.08 km 2 was overlaid with a grid of 500 × 500 m. Fifteen modules were selected and the area of each module served as the sampling site for the entomological survey. Adult and larval stages were sampled. Diversity indices were analyzed to compare mosquito diversity. Rarefaction estimations were used to compare abundance and richness of the mosquito species between different zones. In total, 750 mosquito larvae and 84 resting adults were sampled. Eighteen species of mosquitoes belonging to 11 subgenera and 7 genera were documented. Genera included Aedes (Johann Wilhelm Meigen 1818, Diptera, Culicidae), Anopheles (Johann Wilhelm Meigen 1818, Diptera, Culicidae), Armigeres (Theobald 1901, Diptera, Culicidae), Culex (Carl Linnaeus 1758, Diptera, Culicidae), Lutzia (Theobald 1903, Diptera, Culicidae), and Mimomyia (Theobald 1903, Diptera, Culicidae). Of the 18 mosquito species identified, 8 species are new records for Auroville. The Alpha (α) biodiversity indices show that the mosquito fauna is diverse ( S = 18; D M g = 2.732 [95% CI: 2.732–2.732]). The Shannon-Weiner ( H ʹ = 2.199 [95% CI: 2.133–2.276]) and Simpson indices (λ = 0.8619 [95% CI: 0.8496–0.8723]) measured species richness, evenness, and dominance. The values of these indices suggest high species richness, evenness, and dominance. Prevailing conditions can provide suitable environment for establishment of different mosquito species in this ecosystem. Given the sociodemographic characteristics of this area, research on mosquito diversity and risk of vector-borne diseases will be of great use.